Strategi Pengembangan Fasilitas Kebun Binatang Ragunan Untuk Meningkatkan Kualitas Destinasi - Nurul Nugraha; Wikey Damai Yanti (Jurnal Ilmiah Wahana Pendidikan, 2023)
Ragunan Zoological Park (TMR) is one of the favorite places that also functions as a place for conservation and educational tourism in DKI Jakarta. DKI Jakarta as the capital city of Indonesia is experiencing a decrease in green open space (RTH) which has many benefits for living things. The collection of animals at TMR is quite complete so that it can be an attraction. Ragunan Zoo has a function as conservation, education, tourism and also Green Open Space (RTH) that needs to be maintained. The purpose of this study is to know and understand TMR as a very good object to visit and as an educational place. The analysis process uses the direct observation method by conducting surveys and literature studies. This study was conducted by analyzing the area of the Ragunan Zoo. The results of the analysis can be concluded that TMR in terms of aspects, comfort, security and facilities have an important role for the general public, especially students as a place of conservation and educational tourism in Jakarta